Decomposition analysis and consumer research as essential elements of the new food product development process. Issue 3 (6th March 2017) - Halagarda, Michał
Abstract : Purpose: Due to fast changes in consumer demands and expectations, developing and introducing new products have become a necessity for the food companies in order to survive on the competitive market. The purpose of this paper is to investigate the usefulness of decomposition analysis in combination with consumer research in the new food product development process. Design/methodology/approach: A survey concerning nutritional habits of consumers based on 339 respondents and an analysis of the sensory and nutritional properties of products available on the market have been performed. Findings: It has been indicated that owing to the proposed research methods, a niche in the market can be found. It was found that products currently available on the market do not fully fulfil the essential nutritional and/or sensory criteria. Practical implications: The set of methods used in the study provides a valuable input into the new food product development process. The results of the research show that a company that will deliver a low-caloric bakery savoury snack of high nutritional quality and successfully present its properties to customers may gain a competitive advantage. Originality/value: The topic is relatively new. Other studies focus on complex methods, whereas this research investigates the usefulness of a set of simple but effective tools that can be used in the new food product development process.